Dorsolateral prefrontal lesions do not impair tests of scene learning and decision-making that require frontal-temporal interaction. - Baxter, MG; Gaffan, D; Kyriazis, D; Mitchell, A (2008)
Theories of dorsolateral prefrontal cortex (DLPFC) involvement in cognitive function variously emphasize its involvement in rule implementation, cognitive control, or working and/or spatial memory. These theories predict broad effects of DLPFC lesions on tests of visual learning and memory. We evaluated the effects of DLPFC lesions (including both banks of the principal sulcus) in rhesus monkeys on tests of scene learning and strategy implementation that are severely impaired following crossed unilateral lesions of frontal cortex and inferotemporal cortex. Dorsolateral lesions had no effect on learning of new scene problems postoperatively, or on the implementation of preoperatively acquired strategies. They were also without effect on the ability to adjust choice behaviour in response to a change in reinforcer value, a capacity that requires interaction between the amygdala and frontal lobe. These intact abilities following DLPFC damage support specialization of function within the prefrontal cortex, and suggest that many aspects of memory and strategic and goal-directed behaviour can survive ablation of this structure.